E-Dharmagita Learning Model Innovation with Mobile and Multimedia Technology - Sudana, Oka; Sukma, Kd. Vigyan Melati; Wirdiani, Ayu; Putri, Gusti Agung Ayu (Universitas Negeri Semarang, 2024)
Purpose: Yadnya ceremony is a sacred sacrifice performed with sincere and wholehearted devotion by Hindus to God, spiritual leaders or teachers, fellow humans, the ancestors, and Bhuta_Kala. The implementation of the Yadnya ceremony is_usually accompanied by a spiritual chant of the Hindus known as Dharmagita. Nowadays, a lot of young generations do not know and are even more indifferent to the Dharmagita. Using books as a source of Dharmagita information is less attractive since there are no audio examples or recordings of correct songs that can be listened to. The Android-based e-Dharmagita application was built to overcome these problems to facilitate the younger generation in getting more interesting information about Dharmagita.Methods: e-Dharmagita was constructed with the support of mobile and multimedia technology. In addition, the information presented was related to the Yadnya Ceremony by implementing a complex Tree Algorithm.Results: This research produced an e-Dharmagita Application, of which user acceptance testing using the PSSUQ Method resulted in a score incudes in the excellent category. Therefore, the application could be accepted well in the implementation the Information Technology in Balinese Culture and Hinduism, especially the innovation of a more modern and attractive Dharmagita learning model.Novelty: The Dharmagita learning model using a mobile application is a new model that has not existed before.